Kotak Harta Karun: Media Pembelajaran Numerasi Berbasis AI dan Pola Berpikir Komputasi Anak Usia Dini - Kamiliyah, Zahirotul; Faruk, Roizatul; Charizah, Minnatin (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Early childhood education strives to prepare a generation that is not only academically intelligent, but also has strong computational thinking and numeracy skills. This study aims to explore the use of artificial intelligence-based numeracy learning media in developing computational thinking patterns in early childhood. The method used is qualitative descriptive, with literature studies to understand the phenomenon and design relevant learning applications. The steps in media development include needs, design analysis, interactive content creation, implementation, and revision based on feedback. The designed learning media, such as